2021
DOI: 10.1021/acs.est.1c04388
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Isotope Fractionation by Internal Demethylation and Biomineralization Reactions in Seabirds: Implications for Environmental Mercury Science

Abstract: A prerequisite for environmental and toxicological applications of mercury (Hg) stable isotopes in wildlife and humans is quantifying the isotopic fractionation of biological reactions. Here, we measured stable Hg isotope values of relevant tissues of giant petrels (Macronectes spp.). Isotopic data were interpreted with published HR-XANES spectroscopic data that document a step-wise transformation of methylmercury (MeHg) to Hg-tetraselenolate (Hg(Sec)4) and mercury selenide (HgSe) (Sec = selenocysteine). By ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(66 citation statements)
references
References 52 publications
6
51
0
Order By: Relevance
“…This interpretation conflicts with two recent Hg isotope studies performed on 22 petrel tissues from 8 individuals and 89 whale tissues from 28 individuals [4,15]. The δ 202 Hg value of a tissue (δ 202 Hgt) is the weighted sum of the MDF of each Hg species (Spi) expressed as follows:…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…This interpretation conflicts with two recent Hg isotope studies performed on 22 petrel tissues from 8 individuals and 89 whale tissues from 28 individuals [4,15]. The δ 202 Hg value of a tissue (δ 202 Hgt) is the weighted sum of the MDF of each Hg species (Spi) expressed as follows:…”
mentioning
confidence: 82%
“…in which f(Spi)t is the fractional amount of species i in tissue t, and δ 202 Spi is the species-specific MDF. Through a mathematical inversion analysis of the petrel and whale isotopic data, Manceau et al [4,15] showed that the 22 δ 202 Hgt petrel values and the 89 δ 202 Hgt whale values, could be calculated with just three δ 202 Spi values, each associated with the MeHgCys, Hg(Sec)4, and HgSe species. Therefore, Equation 1 was reduced to We show below that the Queipo-Abad et al [1] data can be reinterpreted in light of the findings of the recent petrel and whale studies [4,15], which concluded that the three Hg species have a specific isotopic composition which is homogenized throughout the body.…”
mentioning
confidence: 99%
“…Given that tissues often contain MeHg and one or more inorganic Hg species, product–reactant isotopic enrichment factors (ε p/r ) have been determined mathematically on tissues analyzed for both chemical speciation and stable Hg isotope data. 58 , 59 The demethylation of MeHg to Hg(Sec) 4 results in isotopically lighter Hg(Sec) 4 due to MDF from a kinetic isotope effect, with δ 202 Hg of product Hg(Sec) 4 being 2.2 to 4.1‰ depleted relative to the reactant MeHg (δ 202 Hg ε p/r = −2.2 to −4.1‰). 58 , 59 Conversely, the biomineralization of HgSe from Hg(Sec) 4 results in a positive MDF (δ 202 Hg ε p/r = +1.6 ± 0.1‰) in the HgSe product relative to Hg(Sec) 4 as observed in the kidney and liver of seabirds ( Figure 1 a).…”
Section: Mercury Isotope Dynamics In Biotamentioning
confidence: 99%
“… 58 , 59 The demethylation of MeHg to Hg(Sec) 4 results in isotopically lighter Hg(Sec) 4 due to MDF from a kinetic isotope effect, with δ 202 Hg of product Hg(Sec) 4 being 2.2 to 4.1‰ depleted relative to the reactant MeHg (δ 202 Hg ε p/r = −2.2 to −4.1‰). 58 , 59 Conversely, the biomineralization of HgSe from Hg(Sec) 4 results in a positive MDF (δ 202 Hg ε p/r = +1.6 ± 0.1‰) in the HgSe product relative to Hg(Sec) 4 as observed in the kidney and liver of seabirds ( Figure 1 a). A separate study by Queipo-Abad et al that measured δ 202 Hg of HgSe isolated from bird liver tissues largely agreed with the value of δ 202 Hg of HgSe determined by a combination of X-ray and isotope analyses (∼0.2‰).…”
Section: Mercury Isotope Dynamics In Biotamentioning
confidence: 99%
See 1 more Smart Citation